2004
DOI: 10.1177/082585970402000108
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Caregiver Burden among Caregivers of Terminally Ill Patients with Cancer

Abstract: Objective To identify factors associated with caregiver burden among those caring for terminally ill patients with cancer. Design Cross-sectional study of interviews with primary caregivers (n=206) of consecutive patients with cancer enrolled in the largest hospice in Connecticut. Methods Data were collected on the caregivers’ sociodemographic characteristics, social network index, and number of restrictions in their own activities due to their caregiving role. The outcome was a nine-item questionnaire ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
98
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 25 publications
8
98
1
6
Order By: Relevance
“…The data indicate that younger caregivers of patients with low-grade tumors experience and report more stress. This data correspond to findings already reported on general cancer caregiver population [4,11,17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The data indicate that younger caregivers of patients with low-grade tumors experience and report more stress. This data correspond to findings already reported on general cancer caregiver population [4,11,17].…”
Section: Discussionsupporting
confidence: 93%
“…However, when looking at descriptive means, caregivers who attended college report more stress than those who have not, high school (0.277), college (0.879), and graduate school (0.710), indicating that caregivers with more education experience and report more stress. These data contradict other data for general cancer caregiver population, which indicate that lower levels of education correlate to higher stress [6,11]. When looking at the relationship between caregiver stress and education by tumor grade, despite educational level attained, caregivers of patients with grade I/II tumors report twice as much stress as their grade III/IV counterparts (0.56 vs 1.06).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…It is specific to the care and varies from anxiety and depression to other emotional and more general responses (Given et al, 2001). Caregiving burden includes physical (Fletcher et al, 2008;Mosher et al, 2013;Osse et al, 2006;Stenberg et al, 2010), psychological (Braun et al, 2007;Deshields et al, 2012;Grunfeld et al, 2004;Mosher et al, 2013;Osse et al, 2006;Song et al, 2011;Stenberg et al, 2010;Williams and McCorkle, 2011), social (Deshields et al, 2012;Goldstein et al, 2004;Song et al, 2011), and financial domains (Deshields et al, 2012;Song et al, 2011;Yun et al, 2005). Physical burden such as sleep disturbance, fatigue and pain were often experienced by caregivers (Fletcher et al, 2008;Osse et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Studies have demonstrated that social and psychological resources are central to succeeding in the caregiver role [22]. Lack of social support is associated with lower quality of life [23] and higher burden [24]. Support in providing the caregiver role may mean caregivers are better equipped to carry out the role, as caregivers who do not have support are more likely to have a patient with unmet needs [25].…”
mentioning
confidence: 99%